El nexo de desarrollo entre convergencia y cohesión: retos para la ampliación europea en el espacio económico global. The development connection between convergence and cohesion: challenges for european expansion in the global economic sphere - Vaitsos, Konstantinos (Papeles del Este, 2006)
The article differentiates between convergence, which originates in the processes of integration, and cohesion, much more complex and systematic. The paths of convergence do not necessarily have to contribute, and they can even reject, socioeconomic cohesion. The dynamic of convergence and cohesion is analysed from two different conceptual focuses: economic geography and the endogenous nature of economic profit. What has occurred in the EU in the last two decades underscores the simultaneous existence of dual results regarding convergence and cohesion, which are not transitory and which, in the context of today’s technological changes, require keeping in mind that greater cohesion is an integral part of global growth.